Effectiveness of Balloon Sinuplasty Compared to Functional Endoscopic Sinus Surgery in The Management of Chronic Rhinosinusitis - Cecilia Gritce Widjaja, Maria; Fauzi, Ahmad (Jurnal Sehat Indonesia (JUSINDO), 2026)
This study addresses the growing clinical interest in minimally invasive surgical approaches for managing chronic rhinosinusitis (CRS), particularly the use of Balloon Sinuplasty (BSP) as an alternative to Functional Endoscopic Sinus Surgery (FESS). While FESS remains the gold standard for severe CRS, BSP has gained attention due to its reduced invasiveness and faster recovery. The purpose of this study is to compare the effectiveness of BSP and FESS in improving clinical outcomes among CRS patients. This research employed a descriptive-analytical literature review approach by analyzing scientific articles from databases such as PubMed, Scopus, and Google Scholar. Selected studies include randomized controlled trials, cohort studies, and meta-analyses that meet established inclusion criteria. Key variables assessed include symptom improvement, quality of life, complication rates, sinus patency, and recovery time. The findings indicate that both BSP and FESS significantly improve symptoms and quality of life, with comparable outcomes in selected patient populations. BSP demonstrates advantages in terms of lower complication rates, reduced intraoperative bleeding, and shorter recovery time, while FESS remains more effective in severe or complex cases involving nasal polyps. In conclusion, both procedures are effective treatment options for CRS, and the choice of intervention should be individualized based on disease severity, anatomical factors, and patient characteristics to achieve optimal clinical outcomes